Restoring The Golden Glory: Tracing The Implementation of Dinar-Dirham In The Financial System of Prophet Muhammad And its Significance as a Global Currency - Muhammad Syahrul Hidayat; Aksana, Didik Supardana Setia; Mazidah, Nurul; Ritonga, Iskandar; Nurhayati (LPPM, Universitas Islam Syarifuddin Lumajang, 2024)
This study explores the concept of Dinar and Dirham, their use during the Prophet's era as mediums of exchange, evaluates their strengths and weaknesses, and analyzes their potential as international currencies to address currency crises and inflation. A qualitative method is employed in this study, involving the collection and analysis of data from various literary sources through a descriptive analysis approach. The research findings reveal that Dinar and Dirham, although adopted from Roman and Persian cultures, were chosen due to the robust stability provided by gold as the underlying value of Dinar. However, the use of Dinar and Dirham cannot directly serve as an alternative to address the economic problems caused by currencies. Limited gold supply and vulnerability to criminal misuse are key drawbacks of Dinar and Dirham. Moreover, economic issues and crises stem not only from currency problems but also from various other contributing factors. Nevertheless, the reintroduction of the concept of Dinar and Dirham as relevant currencies to address modern currency crises is still worth considering. With a clear understanding of their strengths and weaknesses, and careful management of related issues, Dinar and Dirham have the potential to help address today's global currency crises and inflation.